2009
DOI: 10.1111/j.1749-6632.2008.03945.x
|View full text |Cite
|
Sign up to set email alerts
|

Combining Multiple Results of a Reverse‐Engineering Algorithm: Application to the DREAM Five‐Gene Network Challenge

Abstract: The output of reverse engineering methods for biological networks is often not a single network prediction, but an ensemble of networks that are consistent with the experimentally measured data. In this paper, we consider the problem of combining the information contained within such an ensemble in order to (1) make more accurate network predictions and (2) estimate the reliability of these predictions. We review existing methods, discuss their limitations, and point out possible research directions towards mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…For example, edges can be aggregated by using a majority vote (an edge is included only if it is predicted by more than a minimum number of groups) or using a scheme that weighs edges predicted by each team according to the team’s Prediction Score or Overall Score. Other methods of aggregation have also been proposed (15, 16). Because only some of the nodes in the provided PKN were measured or manipulated in the HepG2 cell line data, we asked participants to submit HepG1 networks containing only the observable nodes (ligands, measured phosphoproteins, and molecules targeted by the inhibitors) and the edges linking them.…”
Section: Crowdsourcing As a Strategy For Signaling Network Reconstrucmentioning
confidence: 99%
“…For example, edges can be aggregated by using a majority vote (an edge is included only if it is predicted by more than a minimum number of groups) or using a scheme that weighs edges predicted by each team according to the team’s Prediction Score or Overall Score. Other methods of aggregation have also been proposed (15, 16). Because only some of the nodes in the provided PKN were measured or manipulated in the HepG2 cell line data, we asked participants to submit HepG1 networks containing only the observable nodes (ligands, measured phosphoproteins, and molecules targeted by the inhibitors) and the edges linking them.…”
Section: Crowdsourcing As a Strategy For Signaling Network Reconstrucmentioning
confidence: 99%
“…Friedman et al [46] used a resampling approach of a Bayesian network reconstruction algorithm to assess the confidence of inferred parameters. Additionally, Marbach et al [47] showed that a resampling approach applied to a genetic algorithm for network inference was a top performering method in the DREAM2 five-gene network challenge. We show that by using a resampling approach to generate ensembles of networks with our network inference pipeline we can improve the accuracy of our topology predictions.…”
Section: Introductionmentioning
confidence: 99%
“…We therefore chose a consensus approach to predict an ensemble of networks. Consensus prediction approaches have been successfully applied to network reconstruction before [31]. We carry out 100 reconstruction runs with different parameter settings (Table 1) and random seeds.…”
Section: Methodsmentioning
confidence: 99%